Political values in confucius doctrines - Nassimov М O; Paridinova, B Zh. (Journal of Oriental Studies, 2016)
Modern social sciences and the humanities are based on a foundation of philosophical thought of previous years. Historically the first form of interpretation of social reality was religious mythological explanation of the nature of society. Confucius, the founder of the multidimensional ethical and political doctrine. This article explores the morality and politics, the political ideal of a state system, the value of government in teachings.